A Chinese–Canadian Cross-Cultural Investigation of Transformational Leadership, Autonomous Motivation, and Collectivistic Value - Wang, Zheni; Gagné, Marylène (Journal of Leadership & Organizational Studies, 2013)
Synthesizing theories of transformational leadership and self-determination, this research investigated whether transformational leaders (a) promote the autonomous motivation of their subordinates and whether (b) it results in higher autonomous motivation when subordinates hold high collectivistic values. Multilevel data were obtained from work samples in China and Canada. The results showed a positive relation between managers’ transformational leadership and subordinates’ autonomous motivation cross-culturally. Although higher collectivistic values were related to higher autonomous motivation, collectivist values did not significantly moderate the motivational effect of transformational leadership.
Keywords: dept.mgt; peer-reviewed

Servant leadership and employee outcomes: the moderating role of subordinates’ motives - Donia, Magda B.L.; Raja, Usman; Panaccio, Alexandra; Wang, Zheni (European Journal of Work and Organizational Psychology, 2016)
Drawing from implicit leadership theories we advance servant leadership theory by examining moderating mechanisms that explain under what conditions servant leader behaviours impact followers in organizations. Specifically, we focused on the moderating role of subordinates’ motivational orientations—prosocial values or impression management motives—in relationships between servant leadership behaviours and job satisfaction, as well as subordinate organizational citizenship behaviours (OCBs). Using time-lagged data collected from 192 supervisor-subordinate dyads, we found that servant leadership was positively associated with employees’ job satisfaction, but not significantly related to their performance of OCBs. We also found evidence that subordinates’ motives moderate the relationships between servant leadership and outcomes. Specifically, employees high on impression management experienced lower levels of job satisfaction than their lower scoring counterparts. Our findings suggest that servant leadership may not be equally beneficial for all followers. We discuss implications for theory and practice.
Keywords: citizenship behaviours; dept.mgt; employee motives; implicit leadership theories; job satisfaction; peer-reviewed; servant leadership

The Multidimensional Work Motivation Scale: Validation evidence in seven languages and nine countries - Gagné, Marylène; Forest, Jacques; Vansteenkiste, Maarten; Crevier-Braud, Laurence; van den Broeck, Anja; Aspeli, Ann Kristin; Bellerose, Jenny; Benabou, Charles; Chemolli, Emanuela; Güntert, Stefan Tomas; Halvari, Hallgeir; Indiyastuti, Devani Laksmi; et al. (European Journal of Work and Organizational Psychology, 2015)
Self-determination theory proposes a multidimensional conceptualization of motivation comprising autonomous and controlled forms. Whereas autonomous motivation relates positively to individuals’ optimal functioning (e.g., well-being, performance), controlled motivation is less beneficial. To be able to use self-determination theory in the field of organizational behaviour, the Multidimensional Work Motivation Scale was developed and tested using data from 3435 workers in seven languages and nine countries. Factorial analyses indicated that the 19-item scale has the same factor structure across the seven languages. Convergent and discriminant validity tests across the countries also indicate that the psychological needs for autonomy, competence, and relatedness as well as the theoretically derived antecedents to work motivation (e.g., leadership and job design) are predictably related to the different forms of motivation, which in turn are predictably related to important work outcomes (e.g., well-being, commitment, performance, and turnover intentions). Implications for the development of organizational research based on self-determination theory are discussed.
Keywords: Autonomous motivation; Controlled motivation; Cross-cultural; Extrinsic motivation; Intrinsic motivation; Self-determination theory; Validation; Work motivation; dept.mgt